Roles and mechanisms of parasitism in aquatic microbial communities - David G. Biron (Frontiers Research Topics, 2015)
Next Generation Sequencing technologies are increasingly revealing that microbial taxa likely to be parasites or symbionts are probably much more prevalent and diverse than previously thought. Every well studied free-living species has parasites; parasites themselves can be parasitized. As a rule of thumb, there is an estimated 4 parasitic species for any given host, and the better a host is studied the more parasites are known to infect it. Therefore, parasites and other symbionts should represent a very large number of species and may far outnumber those with 'free-living' lifestyles. Paradoxically, free-living hosts, which form the bulk of our knowledge of biology, may be a minority! Microbial parasites typically are characterized by their small size, short generation time, and high rates of reproduction, with simple life cycle occurring generally within a single host. They are diverse and ubiquitous in the environment, comprising viruses, prokaryotes and eukaryotes. This Frontiers Research Topic sought to provide a broad overview but concise, comprehensive, well referenced and up-to-date state of the art for everyone involved with microbial parasites in aquatic microbial ecology.